2014
DOI: 10.1109/tps.2014.2333543
|View full text |Cite
|
Sign up to set email alerts
|

Fine Al2O3Powder Produced by Radio-Frequency Plasma From Aluminum Dross

Abstract: Aluminum dross is generated as a byproduct in aluminum production or aluminum recycling processes. The major chemical composition of aluminum dross is aluminum element, and it has potential as a starting material to produce high-purity fine aluminum oxide (Al 2 O 3 ) powder. In this paper, a radio frequency (RF) plasma synthesis system is designed as a high-temperature source to produce Al 2 O 3 from aluminum dross. As the RF power increased to 3.5 kW, the color of Al 2 O 3 ceramic powder is transferred to pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…A radio-frequency (RF) plasma synthesis system was designed as a high-temperature source to produce Al 2 O 3 with 99.95% of the purity of the powder. The production was from aluminum cast slag and the results indicated the potential for commercialization [46].…”
Section: Aluminum Alloy Formationmentioning
confidence: 99%
See 3 more Smart Citations
“…A radio-frequency (RF) plasma synthesis system was designed as a high-temperature source to produce Al 2 O 3 with 99.95% of the purity of the powder. The production was from aluminum cast slag and the results indicated the potential for commercialization [46].…”
Section: Aluminum Alloy Formationmentioning
confidence: 99%
“…8. The main authors associated with aluminum alloy residue pretreatment are also associated aluminum casting [48][49][50][51][52][53][54][55][56][57][58] aluminum recycling [5,59,60] automotive boards [23,[25][26][27], and especially aluminum alloys [34,[40][41][42][43][44][45][46][47].…”
Section: Recycling Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was reported that the plasma process provides cheaper operation costs (at least 23%) with lower residues than oil/gas burners. Yang et al [108] treated aluminum dross using a radio frequency-based plasma to recover high-purity fine aluminum oxide (with the size of 8 µm). Saravanakumar et al [88] reported using arc plasma to convert dross of aluminum into alumina powder in an eco-friendly manner.…”
Section: Sustainability Of Nano Aluminamentioning
confidence: 99%